Molecular cloning of stress-induced genes of maize (Zea mays L.) using the pcr-select cdna subtraction technique - Ha, Nguyen Thuy; Leipner, Jurg; Stamp, Peter; Guerra-Peraza, Orlene (Academia Journal of Biology, 2014)
Environmental abiotic stresses, such as drought, high-salinity and low temperature, severely impair plant growth and development and limit crop productivity. In order to survive and adapt to these stresses, plants must induce various physiological, bichemical and molecular changes, including the adaptation of the photosynthetic apparatus, changing in the membrane lipid, the activation of calcium influxes and Ca2+-dependent protein kinase cascades, the accumulation of proline, glycine betaine, soluble sugars and increasing the levels of antioxidants. All these changes are accompanied by notable increases or decreases in the transcript level of specific genes. Hence, transcriptional control of stress-regulated genes is a crucial part of plant responses to abiotic stresses; a further characterization of such gene transcripts in plants may help us to understand the molecular basis of the plant response to abiotic stresses and to identify new targets for manipulating biochemical, physiological and developmental processes in plants. To clarify the process of the response of maize to cold stress and to discover maize genes associated with the response pathway(s), genes induced by cold treatment were isolated according to the PCR-select cDNA subtraction method. 18 cold-induced genes (ZmCOI) were detected at 6°C. They were divided into 6 groups, based on their functions. The cold induction of these genes was confirmed by reverse transcriptase-polymerase chain reaction (RT-PCR) analyses. The sequences of these 18 cold-induced genes have been deposited in GenBank under accesion numbers from DQ078760 to DQ078778.